Political detainees ; New hope for Bacolor ; Music borders [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Tackles unaanswered justice for political detainees. The Pinatubo victims continue to rebuild their homes and living a normal life. Peter Loro playing trumpet with one hand and Sarah, a cellist using corrugated plastic hoses as instruments makes music in classical way.
Political detainees (16 min.) -- New hope for Bacolor (13 min.) -- Music borders (16 min.)
VHS
Keywords: Hopkins, Sarah; Loro. Peter; Political prisoners -- Philippines; Civil rights -- Philippines; Disaster victims -- Pinatubo, Mt; Musicians -- Philippines